Gastrin-releasing peptide receptor: a promising new biomarker to identify cervical precursor lesions and cancer - Martina Lichtenfels; Rafaella Almeida Lima Nunes; Rossana Veronica Mendoza López; Camila Alves da Silva; Luiz Carlos Zeferino; Vanesca de Souza Lino; Adhemar Longatto-Filho; Louise De Brot; Silvia Helena Rabelo-Santos; Daniela Baumann Cornelio; Enrique Boccardo; Caroline Brunetto de Farias; et al. (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: This study aimed to verify the relation between gastrin-releasing peptide receptor (GRPR), oncogenic Human Papillomavirus (HPV) and cervical lesions severity. Methods: GRPR mRNA levels were evaluated in cervical cancer-derived cell lines and in primary keratinocytes expressing HPV16 oncogenes by RT-PCR. GRPR protein expression was assessed by immunohistochemistry in organotypic cell cultures derived from keratinocytes transduced with HPV16 oncogenes and in 208 cervical samples, including 59 non-neoplastic tissue, 28 cervical intraepithelial neoplasia grade 3 (CIN3), 44 squamous cell carcinomas (SCC) and 77 adenocarcinomas (ADC). Generic primers (GP5+/GP6+) were used to identify HPV infection in tissue samples. Experiments involving cell lines were analyzed through non-parametric tests (Kruskal Wallis), and Fisher's Exact Test for human tissues samples. All statistical tests were considered significant at p <0.05. Immunohistochemical evaluation was conducted independently and blindly by two observers (AD- LO). Any discordant findings were resolved through discussion to reach a consensus score. Results: GRPR mRNA levels were not increased in cells expressing HPV16 or HPV18 oncogenes. However, at the protein level, GRPR was upregulated in organotypic cell cultures containing HPV oncogenes. Besides, it was identified an association between GRPR expression and cervical lesion severity (p < 0.0001). The detection rate of high-risk HPV DNA was directly correlated with cervical disease. Nonetheless, HPV infection was not directly associated with GRPR in cervical samples. Conclusion: GRPR expression is highly predictive of cervical lesion severity, irrespective of HPV infection and might contribute to improving patient's therapeutic management as well as being used a marker of disease progression.